Prevalence of Rickettsia spp. in Ticks and Serological and Clinical Outcomes in Tick-Bitten Individuals in Sweden and on the Åland Islands - Lindblom, Anders (PLoS One, 2016)
Tick-transmitted diseases are an emerging health problem, and the hard tick Ixodes ricinus is the main vector for Borrelia spp., tick-borne encephalitis virus and most of the spotted fever Rickettsiae in Europe. The aim of the present study was to examine the incidence of rickettsial infection in the southernmost and south central parts of Sweden and the Åland Islands in Finland, the risk of infection in humans and its correlation with a bite of a Rickettsia-infected tick, the self-reported symptoms of rickettsial disease, and the prevalence of co-infection between Rickettsia spp. and Borrelia spp. Persons with a recent tick bite were enrolled through public media and asked to answer a questionnaire, provide a blood sample and bring detached ticks at enlistment and at follow-up three months later. Blood samples were previously analysed for Borrelia spp. antibodies and, for this report, analysed for antibodies to Rickettsia spp. by immunofluorescence and in 16 cases also using Western Blot. Ninety-six (44.0%) of the 218 participants were seropositive for IgG antibodies to Rickettsia spp. Forty (18.3%) of the seropositive participants had increased titres at the follow-up, indicating recent/current infection, while four (1.8%) had titres indicating probable recent/current infection (≥1:256). Of 472 ticks, 39 (8.3%) were Rickettsia sp. positive. Five (31.3%) of 16 participants bitten by a Rickettsia-infected tick seroconverted. Experience of the self-reported symptoms nausea (p = 0.006) and radiating pain (p = 0.041) was more common among those with recent, current or probable infection compared to those who did not seroconvert. Participants who showed seroreactivity or seroconversion to Rickettsia spp. had more symptoms than those who were seronegative. Seven (3.2%) participants showed seroconversion to Borrelia spp., and three (1.4%) of these showed seroconversion to both Rickettsia spp. and Borrelia spp., in accordance with previous studies in Sweden. Symptoms of rickettsial disease were in most of the cases vague and general that were difficult to differentiate from other tick-borne diseases.